17 Level Hybrid Diode Clamped Inverter With Reduced Number of Components - Alsumady , Mohammed; Jaber, Ibrahim; Nusserat , Khalid (Journal of Electronics and Electrical Engineering, 2023)
Multilevel inverters (MLIs) are gaining more interest recently in medium to high power applications. The main problem with various MLI topologies is that they require a large number of switching devices and DC voltage sources while producing a small number of voltage levels. Which results in bulky inverters with high cost and high output voltage/current total harmonic distortion (THD). This paper introduces a new novel asymmetrical 17-level MLI design using two DC voltage sources and a reduced number of switches. This was achieved by combining a voltage summing and subtracting circuit with a modified diode clamped MLI (DC-MLI), which divides the voltage by two. Thus, generating more voltage levels. nearest level control (NLC) is used to produce the switching signals at a switching frequency of 50Hz. The design is tested and simulated using MATLAB/Simulink, the output voltage THD is kept around 5.7%. The obtained results are compared with other recent 17-level topologies, showing that a good improvement is achieved.